2017
DOI: 10.3389/fnmol.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IIA-related Actomyosin Contractility Mediates Oxidative Stress-induced Neuronal Apoptosis

Abstract: Oxidative stress-induced neuronal apoptosis plays an important role in the progression of central nervous system (CNS) diseases. In our study, when neuronal cells were exposed to hydrogen peroxide (H2O2), an exogenous oxidant, cell apoptosis was observed with typical morphological changes including membrane blebbing, neurite retraction and cell contraction. The actomyosin system is considered to be responsible for the morphological changes, but how exactly it regulates oxidative stress-induced neuronal apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 72 publications
(84 reference statements)
3
27
0
Order By: Relevance
“…32 Additionally, NMMHC IIA also has been identified to participate in BBB dysfunction in ischemia stroke, and the NMMHC IIA-actin interaction mediates H 2 O 2 -induced neuronal apoptosis. 8,12 NMMHC IIA is also an attractive therapeutic target in ischemic stroke. Zhao et al found that TRPM7 kinase modulates OGD/R-induced neuronal apoptosis via annexin 1 carried by NMMHC IIA, blocking NMMHC IIA function by its antagonist blebbistatin was found to improve learning and memory in rats after MCAO and could also improve cell viability after OGD/R.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…32 Additionally, NMMHC IIA also has been identified to participate in BBB dysfunction in ischemia stroke, and the NMMHC IIA-actin interaction mediates H 2 O 2 -induced neuronal apoptosis. 8,12 NMMHC IIA is also an attractive therapeutic target in ischemic stroke. Zhao et al found that TRPM7 kinase modulates OGD/R-induced neuronal apoptosis via annexin 1 carried by NMMHC IIA, blocking NMMHC IIA function by its antagonist blebbistatin was found to improve learning and memory in rats after MCAO and could also improve cell viability after OGD/R.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Our previous studies have confirmed that morphological changes in apoptotic cells are dependent on actomyosin cytoskeleton remodeling in H 2 O 2 -treated neurons. 12 When neurons are stimulated by H 2 O 2 , the interaction between NMMHC IIA and F-actin increased, which provided a basis for generating contractile forces, and ultimately leading to membrane blebbing and neuronal apoptosis. However, little is known about the specific function of NMMHC IIA in neuronal apoptosis under ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations